Salivary hormone concentrations and technical-tactical performance indicators in beach volleyball: Preliminary evidence - Costa, Yago; Domingos-Gomes, Jarbas; Lautenbach, Franziska; Hayes, Lawrence; Nakamura, Fabio; Lima, Jefferson; Castellano, Lúcio; Batista, Gilmário (Frontiers in Sports and Active Living, 2022)
The present study aimed to investigate (i) differences in salivary testosterone and cortisol concentrations before, during, and after simulated beach volleyball match, depending on match outcome (winning vs. losing); (ii) the relationship between technical-tactical performance indicators in beach volleyball and salivary hormonal concentrations (i.e., testosterone, cortisol). We hypothesized (i) salivary testosterone concentrations would be greater in winners and salivary cortisol would be lower; (ii) testosterone would associate with positive technical-tactical performance and cortisol would associate with negative technical-tactical performance. Sixteen athletes participated in the study and were grouped according to the result of a simulated game (winners: n = 8; losers: n = 8). Salivary hormone concentration of testosterone and cortisol were measured by enzyme-linked immunosorbent assay (pre-match, post first set, and post-match), and the coefficient of performance and efficiency were used as technical-tactical performance indicators. Regarding testosterone, there was a large effect size for match outcome after the first set (i.e. Winner vs. Losers) and a moderate effect size for the time in winners (pre-match vs. post-match). Regarding cortisol, there was a moderate effect size of time in losers only (pre-match vs. post-match). Moreover, cortisol pre-match was negatively correlated with the offensive performance (attack performance coefficient: r= -0.541; p= 0.030; attack efficiency: r= -0.568; p= 0.022). In conclusion, the effect of match outcome on testosterone and cortisol levels was moderate in winners and losers, respectively. Moreover, resting cortisol concentration appears to be related to a diminished attack technical-tactical performance. However, larger confirmatory studies are required to confirm these data to corroborate winning increases testosterone levels and/or reduces cortisol in a sporting setting.